Polarization Independent Achromatic Meta-Lens Designed for the Terahertz Domain - Gao, Yufei; Gu, Jianqiang; Jia, Ridong; Tian, Zhen; Ouyang, Chunmei; Han, Jiaguang; Zhang, Weili (Frontiers in Physics, 2020)
In recent years, metasurface-based focusing elements have gradually become an indispensable type of terahertz lenses. However, the meta-lens often suffers from chromatic aberration due to the intrinsic dispersion of each element, especially in the broadband application scenarios. In this paper, we design and demonstrate a silicon-based achromatic meta-lens working from 0.6 to 1.0 THz, which is polarization insensitive because of the adopted symmetrical structures. The simulated focal length and the full width at half maximum (FWHM) of the foci at different frequencies prove the achromatic behavior of our meta-lens compared with the chromatic counterpart. We also show that the focus shift incongruence of our design originates from the transmission amplitude distribution of the meta-lens. This article not only provides an achromatic planar lens working at terahertz domain but also reveals the importance of the amplitude distribution in the achromatic metasurface design.